2019
DOI: 10.1007/s11357-019-00112-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of leaky gut are related to inflammation and reduced physical function in older adults with cardiometabolic disease and mobility limitations

Abstract: Intestinal barrier dysfunction is hypothesized to be a contributing determinant of two prominent characteristics of aging: inflammation and decline in physical function. A relationship between microbial translocation (MT), or their biomarkers (lipopolysaccharide binding protein-1 [LBP-1], soluble cluster of differentiation [sCD]-14), and physical function has been reported in healthy older adults, rats, and invertebrates. However, it is not known whether the existence of comorbidities, or clinical intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 50 publications
0
34
1
Order By: Relevance
“…Increased inflammation in older adults is often associated with increased leaky gut indicated by system markers such as LPS binding protein (LBP) and soluble CD14 (sCD14) in circulation/blood that are linked with poor health outcomes (3,5). Interestingly, we found that the feeding of our human-origin probiotic cocktail significantly reduced LBP levels in the serum of older mice compared with their controls ( Figure 3I).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Increased inflammation in older adults is often associated with increased leaky gut indicated by system markers such as LPS binding protein (LBP) and soluble CD14 (sCD14) in circulation/blood that are linked with poor health outcomes (3,5). Interestingly, we found that the feeding of our human-origin probiotic cocktail significantly reduced LBP levels in the serum of older mice compared with their controls ( Figure 3I).…”
Section: Resultsmentioning
confidence: 90%
“…Increased low-grade inflammation is a major risk factor for morbidity and mortality in older adults (3,4) and a hallmark of aging-related comorbidities. Although the precise etiology of increased inflammation in older adults is not known, emerging evidence suggests that abnormally higher intestinal epithelial permeability ("leaky gut") is associated with increased inflammation in older adults (3,5,6). Higher gut permeability leads to influx of antigens, endotoxins, pathogens, and other proinflammatory substances from gut into the blood and lymphatic circulation, leading to systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past two decades have seen an explosion in data regarding intestinal barrier permeability, its myriad causes, and its relationship to inflammation-related pathophysiology [ 73 , 74 , 75 ]. Multiple biomarkers such as zonulin and various claudins have been identified as useful markers in characterizing the nature of barrier injury [ 76 , 77 ]. Data regarding elevated circulating BDG, its correlation with other markers of microbial translocation and inflammation, and orthogonal testing with enteral polysaccharides such as fluorescein labeled dextran demonstrate that it is also a translocated entity [ 78 , 79 , 80 ].…”
Section: Major Sources Of Circulating Bdgmentioning
confidence: 99%
“…39,40 Importantly, intestinal barrier dysfunction is commonly observed in aging vertebrates and invertebrates. [41][42][43][44][45] A current hypothesis is that decreasing intestinal barrier function with aging can cause increased microbial translocation into the systemic blood circulation, that subsequently causes systemic inflammation (inflammaging) and significant clinical outcomes (e.g., metabolic syndrome, decreased physical function, and mortality).…”
Section: The Common Thread In Chronic Conditionsmentioning
confidence: 99%